The Effect of Profitability, Liquidity, and Asset Structure on Capital Structure with Firm Size as Moderating Variable - Dewi, Cicilia Ratna; Fachrurrozie, Fachrurrozie (Accounting Analysis Journal, 2021)
The purpose of this research is to analyze the effect of profitability, liquidity, and asset structure on capital structure with firm size as a moderating variable. The population of this study was all property and real estate companies listed on the Indonesian Stock Exchange (IDX) from 2014-2016. The number of samples used was 39 companies with the audit of analysis of 117. This study used secondary data taken from the annual financial statements. The method of data analysis was descriptive analysis and Moderated regression analysis by difference absolute value test. The data analysis used was IBM SPSS Statistics 21. The result of the study showed that profitability, liquidity, and asset structure had negative and significant effects on capital structure. Firm size was able to moderates significantly the effect of liquidity on capital structure, but it is not able to moderate the effect of profitability and asset structure on the capital structure. The study concludes that capital structure is influenced by profitability, liquidity, and liquidity that moderated by firm size. Keywords: Profitability; Liquidity; Asset Structure; Capital Structure; Firm Size